2021
DOI: 10.1016/j.sjbs.2021.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of osmotic pretreatment and drying temperature on drying kinetics, antioxidant activity, and overall quality of taikor (Garcinia pedunculata Roxb.) slices

Abstract: Taikor ( Garcinia pedunculata Roxb.) is an underutilized, however nutritious fruit, typically found in Bangladesh and northeast parts of India. Taikor slices (1 ± 0.25 cm thickness) were pretreated for 10 min in 10% sucrose, 10% fructose, and 2% brine solution. Three different temperatures, such as 45, 50, and 55 °C were used to perform the drying operation at 30% constant relative humidity (RH). The thin-layer dehydration characteristics of taikor slices were analyzed using the Newtonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Valadez-Carmona et al [ 53 ] showed that lower temperatures and prolonged duration of treatment maintain an elevated content of cacao pod husk phenolics. Moreover, TFC diminishes as the drying temperature is augmented [ 54 ], as in the case of orange peels [ 55 ], in which a high drying temperature causes the degradation of flavonoids. Esparza-Martínez et al [ 56 ] also described a decrease in the content of non-extractable flavonoids of lime as the drying temperature rises.…”
Section: Resultsmentioning
confidence: 99%
“…Valadez-Carmona et al [ 53 ] showed that lower temperatures and prolonged duration of treatment maintain an elevated content of cacao pod husk phenolics. Moreover, TFC diminishes as the drying temperature is augmented [ 54 ], as in the case of orange peels [ 55 ], in which a high drying temperature causes the degradation of flavonoids. Esparza-Martínez et al [ 56 ] also described a decrease in the content of non-extractable flavonoids of lime as the drying temperature rises.…”
Section: Resultsmentioning
confidence: 99%
“…Pinar et al (2021) found the effects of different drying methods on the drying kinetics of different pepper varieties. Hossain et al (2021) use multiple models, such as Newton, to reveal the thin dewatering characteristics of Tailor. This was also observed by Ataides et al (2022) for Araticum fruits used multiple models to predict drying properties.…”
Section: Introductionmentioning
confidence: 99%
“…Melon color parameters are shown in Table 5. The lower value of L * indicates darkness (Hossain et al, 2021). Fresh samples presented a significantly higher luminosity ( L *) ( p < 0.05) compared to the dried samples, which indicates a reduction in brightness after drying.…”
Section: Resultsmentioning
confidence: 99%